2004
DOI: 10.1158/0008-5472.can-03-3363
|View full text |Cite
|
Sign up to set email alerts
|

An Increase in the Expression of Ribonucleotide Reductase Large Subunit 1 Is Associated with Gemcitabine Resistance in Non-Small Cell Lung Cancer Cell Lines

Abstract: The mechanisms of resistance to the antimetabolite gemcitabine in non-small cell lung cancer have not been extensively evaluated. In this study, we report the generation of two gemcitabine-selected non-small cell lung cancer cell lines, H358-G200 and H460-G400. Expression profiling results indicated that there was evidence for changes in the expression of 134 genes in H358-G200 cells compared with its parental line, whereas H460-G400 cells exhibited 233 genes that appeared to be under-or overexpressed compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
200
3
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 255 publications
(218 citation statements)
references
References 27 publications
12
200
3
3
Order By: Relevance
“…This result supports the previous report that RRM1 is the marker predicting resistance to gemcitabine in lung cancer cell lines (Davidson et al, 2004). In this study, KLM1 gemcitabine-resistant cells had no dCK deficiency in contrast to the lack of dCK in PCI43 and PK1 gemcitabine-resistant cells.…”
Section: Discussionsupporting
confidence: 92%
“…This result supports the previous report that RRM1 is the marker predicting resistance to gemcitabine in lung cancer cell lines (Davidson et al, 2004). In this study, KLM1 gemcitabine-resistant cells had no dCK deficiency in contrast to the lack of dCK in PCI43 and PK1 gemcitabine-resistant cells.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, high expression of the catabolic enzymes 5'-nucleotidase (5'-NT) and cytidine deaminase (CDA) has been found in many cell lines resistant to gemcitabine (Eda et al, 1998;Lotfi et al, 2001). non-small cell lung cancer patients with low expression of the M1 subunit of RR (RRM1) significantly benefited from gemcitabine/ cisplatin neoadjuvant chemotherapy (Rosell et al, 2004), while resistance to gemcitabine was observed both in RRM1 and RRM2 overexpressing cells (Goan et al, 1999;Davidson et al, 2004).…”
mentioning
confidence: 99%
“…46 In addition, when reflecting on the potential future of molecular testing in lung cancer, it is important to consider the association of the excision repair cross-complementation group 1 gene and high expression of the ribonucleotide reductase subunit 1 with platinum 47,48 and gemcitabine resistance, respectively. 49 Clearly, the ability to more easily determine mutation status in patients with advanced NSCLC would be invaluable for overcoming the barriers related to the relative or absolute lack of tumor tissue for direct sequencing.…”
Section: Perspective On Mutational Analysismentioning
confidence: 99%